2015
DOI: 10.1039/c5ra09464j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antioxidant activity of DOPA peptidomimetics by a novel IBX mediated aromatic oxidative functionalization

Abstract: DOPA peptidomimetics with stable O-C and N-C covalent bonds between amino acid residues have been prepared by aromatic oxidative functionalization of tyrosine with 2-iodoxybenzoic acid (IBX). The reaction involves the Michael-like nucleophilic addition of different oxygen and nitrogen protected amino acids on a reactive DOPA quinone intermediate. Similar results were obtained in heterogeneous conditions using supported IBX-amide for more runs. Among the novel derivatives, compounds containing glycine residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
(111 reference statements)
0
19
0
Order By: Relevance
“…Preliminary studies showed that DOPA-derived peptidomimetics 2-5 were characterized by an antioxidant activity higher than that of the corresponding DOPA-containing peptides. 20 On the basis of these data, we decided to evaluate the anti-PD effect of peptidomimetics 2-9 (protected and deprotected forms) on DAergic neurons. Since PD is characterized by low content of DA in the basal ganglia nuclei, potential anti-PD drugs should mimic the effects of DA and/or DOPA.…”
Section: Evaluation Of Anti-parkinson Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary studies showed that DOPA-derived peptidomimetics 2-5 were characterized by an antioxidant activity higher than that of the corresponding DOPA-containing peptides. 20 On the basis of these data, we decided to evaluate the anti-PD effect of peptidomimetics 2-9 (protected and deprotected forms) on DAergic neurons. Since PD is characterized by low content of DA in the basal ganglia nuclei, potential anti-PD drugs should mimic the effects of DA and/or DOPA.…”
Section: Evaluation Of Anti-parkinson Activitymentioning
confidence: 99%
“…[15][16][17][18] The replacement of the natural amide bond in peptides with unusual covalent linkages is a general strategy to improve the stability and activity of the molecule. 19 We recently reported the synthesis of DOPA-derived peptidomimetics with stable O-C and N-C covalent bonds by oxidative functionalization of tyrosine with 2-iodoxybenzoic acid (IBX), 20 that is a biomimetic system of tyrosinase. The reaction proceeded through a Michael-like 1,4-addition of oxygen and nitrogen centred aamino acids to reactive DOPA ortho-quinone intermediate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mimetics also act as supportive molecules for drugs. They protect the drug from fast metabolism and also prevent side effects 83 .…”
Section: Antioxidant Activity Of Peptidomimetic Drugsmentioning
confidence: 99%
“…On the other hand, L-DOPA (3,4-dihydroxyphanylalanine) derivatives play a crucial role in the therapy of Parkinson disease (PD) as they increase the BBB penetration capacity of DOPA, which is well known medicine in the treatment of PD since 1960s. The DOPA peptidomimetics with amino acid cross-linked via oxygen atom were prepared and their antioxidant activities were studied [6].…”
Section: Introductionmentioning
confidence: 99%